The Influence of Leadership and Supervisory Style on Work Discipline of OPD X Employees - Intan Purnamasari Rohendi; Maman Suratman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study was conducted to describe the influence of Leadership Style and Supervision on Employee Work Discipline in OPD X Employees. The research method used is quantitative, with a sample of 53 employees taken from the entire population. The data analysis technique used is multiple linear regression analysis through SPSS statistical software version 24. Data presentation is done through literature study, observation, interviews, and questionnaires, which are guidelines for conducting interviews. The study results indicate that Leadership Style and Supervision positively and significantly affect Work Discipline, both partially and simultaneously.